(untitled) (Journal of Human Sciences, 2018)
Translate Genitive from Arabic to English this paper discusses the translation of the Almoudaf wa Almoudaf Alayh (genitive) of Arabic to English. It discusses the its translation including the semi-added from Arabic to English. It also discusses the linguistic differences found in terms of syntax, language and meaning in both languages ??in a comparative way. As the researches focus on the translation from Arabic to English, the paper addresses most of the types of addition (genitive) in Arabic and how it was translated into English and what the translator must take into account so that s/he can transfer the text from the source language to the targeted language with the accuracy possible. The main purpose is to clarify the types added (genitive) in Arabic and the equivalent in English and how there is a difference in the original text. Translators and their readers are not only confused by the inaccuracy of the translation and obtaining meanings, they sometimes are also confused by the errors in conveying the meaning. This requires clarifying the differences between the language of the translated text and the language to which it is translated in all parts of the language. The knowledge of the translator of the two languages is important as it helps him/her to know how to deal with texts from the first language to the target language.